Exterior photo of Cooleemee Plantation, 1949. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 4-10-49 p.D1.
Exterior photo of Cooleemee Plantation, 1949.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth